1993
DOI: 10.1007/bf00863400
|View full text |Cite
|
Sign up to set email alerts
|

Bone metabolism before and after irradiation with ultraviolet light

Abstract: The beneficial effects of ultraviolet light on cutaneous vitamin D synthesis, calcium metabolism, and bone formation are well known. Regarding the increasing fear of side effects from ultraviolet B (UV-B), lamps with less energy in the UV-B range have been developed. Two spectra with differences in the emission of UV-B have therefore been evaluated for their influence on calcium metabolism. A group of 24 healthy male volunteers was subdivided into two treatment groups. Group 1 was exposed to lamps with higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
2
4
1
1
Order By: Relevance
“…This lack of effect on 1,25(OH) 2 D confirm the results of one of our previous investigations (Falkenbach et al 1993), and may be attributed to the tight physiological control which prevents intoxication. 1α-Hydroxylation in the kidney is inhibited by 1,25(OH) 2 D (Larkins et al 1974) and stimulated by PTH (Fraser 1980), so that only in states of severe 1,25(OH) 2 D deficiency with concomitant secondary hyperparathyroidism should a significant increase of 1,25(OH) 2 D be expected after UV radiation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This lack of effect on 1,25(OH) 2 D confirm the results of one of our previous investigations (Falkenbach et al 1993), and may be attributed to the tight physiological control which prevents intoxication. 1α-Hydroxylation in the kidney is inhibited by 1,25(OH) 2 D (Larkins et al 1974) and stimulated by PTH (Fraser 1980), so that only in states of severe 1,25(OH) 2 D deficiency with concomitant secondary hyperparathyroidism should a significant increase of 1,25(OH) 2 D be expected after UV radiation.…”
Section: Discussionsupporting
confidence: 90%
“…There was no significant decrease of serum PTH after UV exposure -as has been observed previously in a study of young, healthy male volunteers (Falkenbach et al 1993) -even in the detailed analysis of either the subjects who had relatively high levels of PTH (>40 pg·ml −1 ) before treatment or those who had not received oral vitamin D supplements. In a previous study (Falkenbach et al 1993) the greatest alteration in bone metabolism was observed to occur 4 weeks after the last dose of UV radiation.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This, however, cannot be the reason as we have previously observed a significant increase of 25 (OH)-vitamin D after a similar protocol of UV treatment (Falkenbach et al 1993).…”
Section: Discussionmentioning
confidence: 48%